PA01.50. Enriching Public Health Through: Nidana Parivarjana and Pathya Apthya w.e.r. to Amavata - Mishra, Nimisha (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Ayurveda is the manual for human body. It tells how to manage this delicate machine properly. According to Sankhya theory (karya karana vada) behind every karya (action) there is karana (cause). The same theory is applied to cropping up of ailments in human body, where the etiopathology responsible for disease is known as Nidana or hetu. “Sankchheptakh kriya yog nidana pariverjanam” (Su.uttartanra. 1) The Nidana (etiopathological factors) responsible for Amavata like viruddhahara, viruddhachesta, mandagni etc. vitiates Agni and annavaha srotusa (abhyantar rog marga), thus triggering an autoimmune response. As the disease and state of aama progresses the disease afflicts the sandhi (Madhayma rog marga) with kricchasadhya or yapya prognosis. METHOD: Comprehensive and analytical study of Ayurvedic literature, research papers and various Journals was carried out to reach the better understanding and cause of disease. RESULT: Mandagni is indispensable factor for aama, so the utmost priority must be to maintain the hemostasis of Agni and clear the path (Srotus) of body, by avoiding the causative factors and following dietetic pattern as described. “Ruksha swedo…………. Aamvatmayine hitani” (bhaisajya Ratnawali 26) CONCLUSION: It is well known that the disease Amavata is incurable and relapsing in nature. So being an Ayuvedician it should be our responsibility to redeem its normal state with the help of nidana parivarjan and judicious use of pathya apathya. It will not merely avert the disease, but also enrich public health through Ayurveda.